An actuated force feedback‐enabled laparoscopic instrument for robotic‐assisted surgery. Issue 1 (2nd May 2013) - Moradi Dalvand, Mohsen; Shirinzadeh, Bijan; Shamdani, Amir Hossein; Smith, Julian; Zhong, Yongmin
Abstract Background Robotic‐assisted minimally invasive surgery systems not only have the advantages of traditional laparoscopic instruments but also have other important advantages, including restoring the surgeon's hand–eye coordination and improving the surgeon's precision by filtering hand tremors. Unfortunately, these benefits have come at the expense of the surgeon's ability to feel. Various solutions for restoring this feature have been proposed. Methods An actuated modular force feedback‐enabled laparoscopic instrument was proposed that is able to measure tip–tissue lateral interaction forces as well as normal grasping forces. The instrument has also the capability to adjust the grasping direction inside the patient body. In order to measure the interaction forces, strain gauges were employed. A series of finite element analyses were performed to gain an understanding of the actual magnitude of surface strains where gauges are applied. The strain gauge bridge configurations were calibrated. A series of experiments was conducted and the results were analysed. Results The modularity feature of the proposed instrument makes it interchangeable between various tip types of different functionalities (e.g. cutter, grasper, dissector). Calibration results of the strain gauges incorporated into the tube and at the base of the instrument presented the monotonic responses for these strain gauge configurations. Experimental results from tissue probing and tissue characterization experiments verified the capability of the proposed instrument in measuring lateral probing forces and characterizing artificial tissue samples of varying stiffness. Conclusion The proposed instrument can improve the quality of palpation and characterization of soft tissues of varying stiffness by restoring sense of touch in robotic assisted minimally invasive surgery operations. Copyright © 2013 John Wiley & Sons, Ltd.